An Empirical Evaluation of a Generative Method for the Expression of Personality Traits through Action Choice - Bahamon, Julio; Young, R. (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2017)
The presence of interesting and compelling characters is an essential component of effective narrative. Well-developed characters have features that enable them to significantly enhance the believability and quality of a story. In this paper, we describe the results of an experiment to evaluate a planning-based narrative generation system that focuses on the generation of stories that express character. The system is designed to automatically produce narratives that show character personality traits through the choices characters make when selecting the means by which they achieve their goals. Results from our study support the hypothesis that an audience presented with stories generated by Mask will attribute personality traits to the story characters that have significant correlation with the computational model of personality used to drive the characters’ choices.